Synchronous collaborative writing impact on students' individual writing competence - Alwahoub, Husam Masaoud
The introduction of Web 2.0 and its tools (i.e., Google Docs and Wikis) has brought a new perspective to computer-assisted collaborative writing in second language (L2) and foreign language (FL) contexts. Studies on L2 writing have highlighted the vibrant role of computer-based collaborative writing activities and web-based tools in developing learners' writing abilities. However, most of these studies have been at the tertiary level; therefore, a need arises to conduct similar studies in a mainstream K-12 setting. Accordingly, this study aims at examining the impact of the synchronous collaborative writing on developing students' individual writing performance and quality, as well as identifying students' perceptions towards these activities and tools in the mainstream K- 12 classes. The study used a quasi-experiment and a convenience sampling that included 49 EFL fourth grade students in a private primary school in Saudi Arabia. The data were collected from students' pre- and post-tests of three individual writing tasks (Narrative, Argumentative, and Informative) and a post-treatment questionnaire. Students' tests were assessed using a human-based scoring rubric and an online scoring tool (Coh Metrix). All numerical data were calculated for descriptive statistics using IBM SPSS Statistics 23, where independent samples r-test was employed to analyse students' tests. The analysis of the individual writing performance in the pre- and post-tests showed that the total mean scores of the content, language use, and organisation measurements increased in both the experimental (collaborators) and control (traditional writing) groups. In addition, significant differences existed in the three writing tasks in the post test scores of the experimental group. Also, significant differences occurred in the post test scores between the groups; the collaborators group scored higher than the traditional writing group. However, no significant difference was revealed between the pre- and post-test scores of the control group. Second, the analysis of the individual writing quality failed to show a significant difference in the mean scores of the three writing tasks and most of the three measurements, namely lexical diversity, syntactic complexity, and textual cohesion in both groups. However, both the textual cohesion measurement in the narrative task and the lexical diversity measurement in the informative task showed significant differences in support of the collaborators. Moreover, there were score gains in the post-tests of many measurements in both groups, which confirms the vital role of the task type variable in collaborative writing. Third, the analysis of the respondents' responses based on the survey revealed positive per ptions (M=4.22) stating that collaborative writing promoted their knowledge and inti rrnatlon and improved their writing skills. They added that this experience m tivated their learning environment, inspired them to study more, and increased their interaction skills. This study contributes to the limited literature of synchronous collaborati ve writing in the mainstream K -12 classes. The study also suggests the use of scaffolded collaborative tasks within the Web 2.0 technology to expedite a better learnin experience as well as extend the possibility of FL writing development and individual linguistic growth.